FACTORS INFLUENCING SUSTAINABILITY REPORT DISCLOSURE ON MINING COMPANIES LISTED IN IDX - Karundeng, Mourend Gabriella; Salim, Susanto (International Journal of Application on Economics and Business, 2023)
The goal of this study is to examine how the composition of the board of commissioners, the percentage of independent commissioners, company size, leverage, and liquidity affect the publication of sustainability reports by mining companies that are listed on the Indonesia Stock Exchange between 2017 and 2020. Eight people were chosen as the sample for this study using the purposive sampling method. The EViews version 12 application is used to process the data in this study. The findings of this study suggest that corporate size and liquidity have a substantial impact on the disclosure of sustainability reports. Contrarily, the variables governing the board of commissioners, the percentage of independent commissioners, and leverage have no impact on the disclosure of sustainability.